1994
DOI: 10.1161/01.res.75.1.149
|View full text |Cite
|
Sign up to set email alerts
|

T-type Ca2+ channels are abnormal in genetically determined cardiomyopathic hamster hearts.

Abstract: Although there is substantial evidence of abnormal Ca2+ homeostasis in heart cells of the cardiomyopathic Syrian hamster (Bio 14.6 strain), the mechanism by which these myocytes become Ca2'-overloaded is not Ca2+ currents were measured in cardiomyopathic (Bio 14.6 strain) and normal control (FIB) cardiac myocytes.We report here that both L-and T-type Ca> channels were present in ventricular myocytes isolated from 200-to 300-day-old cardiomyopathic and age-matched normal hamsters. The mean current density of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(79 citation statements)
references
References 31 publications
2
76
1
Order By: Relevance
“…With the utilization of intracellular calcium indicators, intracellular calcium transients can be recorded in multicellular preparations and in isolated myocytes. The spontaneously hypertensive rat model and Syrian hamster model have been extensively investigated with regard to [Ca 2+ ] i handling (Bing et al 1988;Brooks et al 1994Brooks et al ,1997Brooksby et al 1992Brooksby et al , 1993Finkel et al 1987;Pfeffer and Frohlich 1973;Sen and Smith 1994;Sen et al 1990). Rodent models, like all animal models, however, have limitations Gwathmey andDavidoff 1993,1994).…”
Section: Discussionmentioning
confidence: 99%
“…With the utilization of intracellular calcium indicators, intracellular calcium transients can be recorded in multicellular preparations and in isolated myocytes. The spontaneously hypertensive rat model and Syrian hamster model have been extensively investigated with regard to [Ca 2+ ] i handling (Bing et al 1988;Brooks et al 1994Brooks et al ,1997Brooksby et al 1992Brooksby et al , 1993Finkel et al 1987;Pfeffer and Frohlich 1973;Sen and Smith 1994;Sen et al 1990). Rodent models, like all animal models, however, have limitations Gwathmey andDavidoff 1993,1994).…”
Section: Discussionmentioning
confidence: 99%
“…T-type currents have been found to be increased twofold in cardiomyopathic Syrian hamsters relative to other hamster strains (46,362). Studies using 8-mo-old animals found that the voltage dependence of activation and inactivation was shifted to more negative potentials in ventricular myocytes from cardiomyopathic animals (362). In contrast, studies using 1-day-old hamsters found that only inactivation was shifted (46).…”
Section: Properties Of T-type Currents In Peripheral Tissuesmentioning
confidence: 96%
“…T-type currents are also reexpressed in dedifferentiated rat ventricular myocytes (114). T-type currents have been found to be increased twofold in cardiomyopathic Syrian hamsters relative to other hamster strains (46,362). Studies using 8-mo-old animals found that the voltage dependence of activation and inactivation was shifted to more negative potentials in ventricular myocytes from cardiomyopathic animals (362).…”
Section: Properties Of T-type Currents In Peripheral Tissuesmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, recent reports suggest that the reexpression of the T-type calcium channel in the failing heart may contribute to cardiac hypertrophy, 32 to remodeling after myocardial infarction 33,34 and to the development of cardiomyopathy. 35 In this study, LVMI, an important surrogate marker, 36 was significantly decreased after 18 months in the efonidipine group with the sustained reduction of ALD. Taken together with our findings, T-type calcium channel blockers such as efonidipine may be useful for the management of hypertension in patients with CHF.…”
mentioning
confidence: 47%